International trade and pollution in shared resources: A study of international rivers - Hilary Sigman (Rutgers University, Department of Economics, 2002)
This paper examines whether trade relationships facilitate resolution of international environmental spillovers. Trade might promote cooperation by providing opportunities for implicit side payments, allowing linkage between nvironmental and trade concessions, providing direct leverage over other countries' production, or instilling a perception of shared goals. Using data from the UN's Global Environmental Monitoring System (GEMS) on water quality in international rivers, the paper examines the influence of bilateral trade on pollution in rivers that cross international borders. In equations with country fixed effects, the paper finds evidence of lower water pollution in rivers shared between countries with more extensive trade.
Keywords: F18; Q56; 330; Environment; Transboundary pollution; Water quality; Grenzüberschreitende Umweltbelastung; Außenwirtschaft; Gewässerbelastung; Internationale Umweltpolitik; Welt